Health Reproductive Health Services and Its use in Public Health Center Areas of Kupang City - Yuliana Dafroyati (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2017)
Background: Adolescence is one of the most critical periods in the human life cycle, so a teenage reproductive health service center is needed to provide guidance and health services. Access and acceptability of adolescents in adolescent reproductive health services is lacking. The problem faced by Kupang City Health Office is the program of health care for adolescents (PKPR) is not maximally run in the health center and is still socialized in schools working area of Public Health Center but not all schools, so access teenager to reproductive health problem is still low. Objective: To know the relation of access and acceptability of health service to utilization of reproductive health service of adolescent at Kupang City Health Center. Research Method: Cross-sectional design with quantitative and qualitative approach. Qualitative data were collected by in-depth interview technique. Sampling with simple random sampling. The subject is 110 high school students in the community health centers that have opened adolescent reproductive health service centers. Results: The proportion of adolescent reproductive health service utilization was 26.4%. Bivariable analysis showed a significant relationship between health service access with the utilization of adolescent reproductive health service with p-value <0,05, RP value 20,67 in 95% CI between 4.59-92,99 mean adolescent that utilize reproduction health service Has a 20.67 times greater likelihood in adolescents whose access to health care is easier than in adolescents whose access to health care is difficult. Descriptively, most teenagers need service (85.5%), and have positive attitude (82,7%) and have expectation of reproductive health service at Public Health Center (72,7%). Conclusions: The prevalence of adolescents utilizing reproductive health services is greater in adolescents with access to health care easier than in adolescents whose access to health care is difficult. Acceptability of health services also affects adolescents to utilize reproductive health services.